Pengaruh Model Pembelajaran Kooperatif Tipe TGT (Team Games Tournament) terhadap Kemampuan Pemahaman Konsep Matematika Siswa: Penelitian - Fitrianti Fitrianti; I Wayan Sudane; Nur Fajrah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the effect of the TGT (Team Games Tournament) type cooperative learning model on students' mathematical concept understanding ability in one of the public senior high schools in Kintom District. The research subjects were 21 students of class XI MIPA2. The method used was pre-experimental with a one group pretest-posttest design. Data were collected through pre-test and post-test, where the test was given before and after the treatment. Furthermore, it was analyzed using descriptive and inferential statistics (normality test, homogeneity, and t-test). The results of the study are shown in the Paired Sample Test table, the sig. value is 0.000 ˂ 0.05 so that H0 is rejected and H1 is accepted. Therefore, it is concluded that the TGT type cooperative learning model is an effective strategy to improve the ability to understand mathematical concepts.